The knowledge of registered nurses regarding skin integrity, foot care and nutrition of a diabetic client with a stroke - Jordaan, Danielle Nicolene (Stellenbosch : Stellenbosch University, 2012)
Thesis (MPhil)--Stellenbosch University, 2004.